2020
DOI: 10.1039/d0ra01017k
|View full text |Cite
|
Sign up to set email alerts
|

Simulated spatial radiation impacts learning and memory ability with alterations of neuromorphology and gut microbiota in mice

Abstract: Exposure to 60Co-γ ray impacts learning and memory ability as well as the cell morphology and neurotransmitters in hippocampus, even disrupts the bacterial community in colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…The brain is highly sensitive to radiation, which usually causes a decline in learning and memory 28,29 . Our previous study also confirmed this conclusion 30 . AS is a kind of wild herb with the homology of medicine and food.…”
Section: Discussionsupporting
confidence: 77%
“…The brain is highly sensitive to radiation, which usually causes a decline in learning and memory 28,29 . Our previous study also confirmed this conclusion 30 . AS is a kind of wild herb with the homology of medicine and food.…”
Section: Discussionsupporting
confidence: 77%
“…The hippocampus consists of anatomically different but functionally related subdomains containing different cell types (Xu et al, 2022; Zhao et al, 2008). The dentate gyrus (DG) is one of two brain regions where neurogenesis occurs throughout life (Zhao et al, 2008), and the DG is particularly sensitive to radiation (Mizumatsu et al, 2003; Monje, 2008; Schultz & Rolls, 1999; Song et al, 2020). However, compared with those in other brain regions, the neurons within the CA1 region are the most sensitive to neurodegeneration associated with Alzheimer's disease or ischemic episodes (Mizumatsu et al, 2003; Monje, 2008; Schultz & Rolls, 1999; Soltesz & Losonczy, 2018, Song et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The dentate gyrus (DG) is one of two brain regions where neurogenesis occurs throughout life (Zhao et al, 2008), and the DG is particularly sensitive to radiation (Mizumatsu et al, 2003; Monje, 2008; Schultz & Rolls, 1999; Song et al, 2020). However, compared with those in other brain regions, the neurons within the CA1 region are the most sensitive to neurodegeneration associated with Alzheimer's disease or ischemic episodes (Mizumatsu et al, 2003; Monje, 2008; Schultz & Rolls, 1999; Soltesz & Losonczy, 2018, Song et al, 2020). Currently, there are no systematic studies about the molecular changes within the hippocampus after irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Water maze was used to evaluate the learning and memory ability according to our previous method 46 . Briefly, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%